HOW DEPRESSIVE ARE OUR ELDERLY POPULATION? – A PREVALENCE STUDY IN A SLUM OF WEST BENGAL. - DR.GAUTAM DHAR (International Journal of Pharma and Bio Sciences, 2013)
Prevalence of mental depression among the elderly is gradually increasing in West Bengal along with other part of the world. A community based cross-sectional study was conducted among elderly population in a slum of Medinipur town, West Bengal, India to find out the prevalence of depression and its related factors. 10% of the elderly population (n=204) was selected by systematic random sampling. Yesavage’s Geriatric Depression Scale was used for collecting the data. 59.8% of the subjects were suffering from depression and prevalence increased with age. Prevalence was significantly higher (83.33%) among respondents who were single and/or physically disabled (88.9%). Thus sympathetic and positive attitude to the depressed elderly people by the surrounding people can help the society.